Development and validation of the Australian Midwifery Standards Assessment Tool (AMSAT) to the Australian Midwife Standards for Practice 2018. Issue 2 (March 2020) - Sweet, Linda; Fleet, Julie; Bull, Angela; Downer, Terri; Fox, Deborah; Bowman, Rebekah; Ebert, Lyn; Graham, Kristen; Bass, Janice; Muller, Amanda; Henderson, Amanda
Abstract: Background: The Australian Midwifery Standards Assessment Tool (AMSAT) was developed against the Competency Standards for the Midwife in 2017 to enable consistent assessment of midwifery student performance in practice-based settings. The AMSAT requires revision and re-validation as the competency standards have now been superseded by the Midwife Standards for Practice 2018. Objective: This research revised and validated the AMSAT to assess performance of midwifery students against the Midwife Standards for Practice 2018 and assessed its sensitivity. Design: A mixed-methods approach was used in a two-phase process. Phase one involved the re-wording of the AMSAT and behavioural cue statements in an iterative participatory process with midwifery academics, assessors and students. The tool was field-tested in different assessment environments in phase two. Completed assessment forms were statistically analyzed, whilst assessor surveys were analysed using descriptive statistics and qualitative content analysis. Findings: Analysis of AMSAT (n = 255) indicates the tool as: internally reliable (Cronbach alpha > .9); valid (eigenvalue of 16.6 explaining 67% of variance); and sensitive (score analysis indicating increased levels of proficiency with progressive student experience). Analysis of surveys (n = 108) found acceptance of the tool for the purpose of summative and formative assessment, and in the provision of feedback to midwifery students on their performance. Conclusion: This study demonstrates that the re-developed AMSAT is a valid, reliable and acceptable tool to assess midwifery students' performance against the Australian Midwife Standards for Practice This user-friendly tool can be used to standardize midwifery student assessment in Australia and enable continued benchmarking across education programs.